Starategi Guru Sekolah Minggu Untuk Mempertahankan Karakter Iman Anak Sekolah Minggu Masa Pandemi Covid 19 - Spenerhard Makahinsade (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2021)
This paper is a theological analysis of the situation during the Covid 19 pandemic where the church is not ready to serve the congregation, let alone to hold a Sunday School Children's worship meeting which is held two or three times a week. This will reduce the quality and quality of faith that is loose in the growth and development of faith in Sunday school children. So that the author wants to conduct scientific research during the Covid 19 pandemic by examining "What strategies should be done to maintain the character of the faith of the Sunday School children of the GMIM Golgota congregation during the Covid 19 pandemic.For Sunday school teachers, teachers fail to keep children's attention to focus on the story of God's Word. Within the duration of 10 minutes the children in question were already flying or sleeping. This incident is an anomaly that the learning model or learning method used by Sunday school teachers from across the country has failed to maintain children's interest in worshiping online. In theory, the psychology of the learning process of Sunday school children can only focus on 15 minutes of learning, but the above fact is even shorter (10 minutes), so to be able to maintain Sunday school children's attention on Sunday school worship learning materials, appropriate teaching methods are needed.Parents fail to instill positive Christian attitudes in their children. Why is that ? This illustration shows that the child does not have social merit in following online Worship. Yes, the teacher who teaches far away. Surely there are also many other children who attend Sunday school worship but the child does not hesitate to lift his legs, sleep on a chair and end up literally fast asleep in a chair that should not be a bed. The incident above illustrates how parents fail to educate manners.This study used a descriptive qualitative approach, where the data obtained were in the form of explanations of concepts or text instead of numbers. The results of the study concluded that the strategy of Sunday school teachers to maintain the faith character of Sunday school children in the Gmim Golgota congregation during the COVID-19 pandemic was able to develop the potential of Sunday school teachers to create a method of “Active, Creative, Effective, and Fun Learning in arranging Sunday school worship, building partnerships. holistic stewardship "